Household choices of sanitation infrastructure and impact on disease in India. (October 2022) - Tiwari, Piyush; Tirumala, Raghu Dharmapuri; Shukla, Jyoti
In the recent past, there has been a substantial push to increase the sanitation infrastructure in India to end open defecation and improve level of hygiene. The choice of the type of sanitation, however, depends on demographic, socio-economic, tenurial, cultural and sanitation surroundings, which not only impacts sanitation practices but also incidences of diseases. This paper empirically analyses the determinants of households' choice of toilet facility and the relation between incidence of diseases and sanitation using National Sample Survey Office's 76 th round of the survey for 2018-19. The results indicate that the social, economic and cultural factors have significant impact on the households' choices of a toilet. There is a preference for flush type toilets connected to a sewer among households with better socio-economic status. This research finds that the quality of microenvironment within which a household lives has a significant impact on the incidence of disease. The results imply that the interventions for improved sanitation need to be holistic, emphasising microenvironment improvement and providing better access to sanitation infrastructure and inculcating more hygienic behavioural practices.